Pseudopyropoikilocytosis: a striking artefact. Issue 9 (September 1996) - Bain, B J; Liesner, R
Abstract : The blood films both of patients with hereditary pyropoikilocytosis and of those with severe thermal burns are characterised by budding erythrocytes and the presence of microspherocytes. Recently, a fourth example of similar morphological features, caused by overheating of a blood specimen in a motor vehicle during transport to the laboratory, has been observed. It is important to be aware of this artefact as failure to recognise it is likely to lead to diagnostic confusion and unnecessary further testing, causing inconvenience to the patient.